Outcomes of Traumatic Pancreatic Injuries in Pediatric and Adult Patients: A Retrospective Study Involving Four Trauma Centers - Iurcotta, Toni; Addison, Poppy; Amodu, Leo I.; Akerman, Meredith; Rilo, Horacio L. (Journal of Child Science, 2017)
Traumatic injuries of the pancreas are rare and affect both children and adults. Very little has been done to investigate differences in outcome between these two age groups. We performed a retrospective review of cases in four trauma hospitals to determine the differences in outcomes between pediatric and adult patients with traumatic pancreatic injuries. A retrospective chart review was performed for 69 pediatric and adult patients seen at four trauma centers in our health system between 1990 and 2014. The Mann–Whitney's U-test was used to compare continuous variables, while the chi-square and Fisher's exact tests were used for categorical variables. Mortality was determined using the Social Security Death Master File. In this study, 26 pediatric and 43 adult patients were included. Median ages were 11.4 and 42.3 years, respectively. There were significant differences in mechanism of blunt injury between pediatric and adults (motor vehicle collisions = 17.4 vs. 64.9%, bicycle accidents = 43.5 vs. 0.0%; p-value for both comparisons < 0.0001), median injury severity score (6.5 vs. 12; p = 0.030), surgical management (30.8 vs. 67.4%; p = 0.003), and postinjury pancreatitis (57.7 vs. 20.9%; p = 0.002). Median hospital length of stay was 5 versus 11 days (p = 0.005), respectively. There were no differences in mortality or other complications. In spite of significant differences in blunt injury type, injury severity, and the need for surgery, there were no significant differences in mortality or most postinjury complications between pediatric and adult patients with traumatic pancreatic injuries.
Keywords: adult; pancreas; pediatric